(untitled) (Baltic Journal of Sport and Health Sciences, 2017)
Background. In this research, we aimed to investigate the effects of outdoor camps on orienteering athletes. Methods. The study group consisted of 74 athletes (44 males and 30 females, aged 11.94 ± 1.32 years) who participated in Bolu outdoor camp on the 3 rd –13 th of August, 2015. Interview technique, which is one of the qualitative research methods, was used as data collection tool and content analysis method was used for data analysis. Results. Demographic factors were interpreted after the analysis of the obtained data and three main research questions were discussed under the topics of the views of athletes about the concept of Orienteering which is an outdoor sport, themes and codes regarding the purpose of Orienteering by the students who participated in the outdoor camp, and themes and codes about the outcomes of Orienteering for the students who participated in outdoor camps. Conclusion. It is suggested that a policy must be developed within the Ministry of Youth and Sport and Sport Federations in order to disseminate more deliberate and more comprehensive outdoor education among young people and measures should be taken to provide extensive participation. Keywords: sport, outdoor education, camp, orienteering.